1999
DOI: 10.4269/ajtmh.1999.60.410
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum clinical malaria in Dielmo, a holoendemic area in Senegal: no influence of acquired immunity on initial symptomatology and severity of malaria attacks.

Abstract: Abstract. Six hundred eighty-nine Plasmodium falciparum malaria attacks were observed during a three-year period among 226 inhabitants of the village of Dielmo, Senegal, an area of high malaria transmission. Malaria attacks were defined as clinical episodes with fever (body temperature Ն 38.0ЊC) or reporting of fever or headache or vomiting, associated with a parasite:leukocyte ratio above an age-dependent pyrogenic threshold identified in this population. The symptom frequencies were tested against age, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 29 publications
4
52
0
1
Order By: Relevance
“…In semi-immune children and adults, the peaks of high parasitemia that are responsible for fever are spontaneously controlled within a few hours or days, and symptoms would disappear rapidly even if no malaria treatment were available. 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…In semi-immune children and adults, the peaks of high parasitemia that are responsible for fever are spontaneously controlled within a few hours or days, and symptoms would disappear rapidly even if no malaria treatment were available. 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…This value is within the range commonly used by other investigators. 5,6,12 However, it should be noted from plots of parasitemia and temperature over time (Figure 1), that the parasites elicited a host response reflected by elevations in body temperature at levels much lower then the fever threshold. Thus, different clinical definitions of fever would be expected to alter the results presented.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 In fact, investigators reporting results from sub-Saharan Africa generally only include high densities of P. falciparum parasitemia (adjusted for age) as part of the definition for malaria disease. 6,[23][24][25] Nevertheless, the results of adjusted multiple logistic regression models showed that a clinical diagnosis of malaria by the examining physician: a history of fever, rigors, headache, and an elevated temperature or a palpable spleen in children were all highly associated with the presence of malaria parasites and the density of parasites in the blood in a monotonic dose-response manner. This association was present with either P. falciparum or P. vivax infections although the strength of association was greater with the former.…”
Section: Discussionmentioning
confidence: 99%